United States and Love without Benefits - Pham, Van Quang (Khoa Học Công Giáo và Đời Sống, 2021)
In the world, people are racing with technology, engrossed in work, whirling along daily life, thus losing their connection with each other? Economists are busy in their fields, students have to race with the learning, even there are people who are just absorbed in their own enjoyment needs. They have gradually forgotten the solidarity, sometimes even the meals with family. However, the coronavirus pandemic has changed completely everything, such as economy, education, and daily life, and it takes opportunity to teach us great lessons. This is my three lessons: 1. Humans are easily vulnerable to the power natural disaster without solidarity and love; 2. People need to unite, share and love each other freely; 3. Humans always need the help of God, who creates and keeps each of us in unity and love.